Small-scale production of hydrous ethanol fuel: Economic and environmental assessment. (October 2016) - Mayer, Flávio Dias; Brondani, Michel; Hoffmann, Ronaldo; Feris, Liliana Amaral; Marcilio, Nilson Romeu; Baldo, Vanessa
Abstract: Energy consumption in rural areas and the increasing demand for liquid fuels in Brazil has stimulated the development of alternatives for fuels production, including ethanol. The potential of small-scale ethanol production (SSEP) – up to five thousand litres daily – can help to meet this demand and contribute byproducts to animal feed. This study aims to assess the economic feasibility and environmental impacts of ethanol production at a small-scale distillery with a production capacity of 30 L h −1 of hydrous ethanol fuel (HEF). Regarding cost, three cases were analyzed in which the minimum, average and maximum raw material prices were assessed. The cost of HEF for these cases was US 0.68, 0.92 and 1.16 per litre, respectively, highlighting the cost of the raw materials, which can contribute up to 69% of the total cost. Life cycle Assessment (LCA) shows that agricultural stage is responsible for higher environmental impact in 7 of 11 categories, requiring special attention to minimize potential damage. SSEP has positive energy balance (1.97) only considering bagasse silage as byproduct or replacing firewood by bagasse to generate process heat (7.39). This study demonstrates that without the support of policies that provide economic incentives for HEF production, the small-scale production of HEF will have a secondary role in supplying HEF to meet the demand for liquid fuels in Brazil. Graphical abstract: Highlights: The small-scale production of ethanol can help to meet the demand for liquid fuels. Two scenarios were analyzed in which raw material prices were assessed. Average price of raw material results in US 0.92 L −1 of ethanol. LCA and EEA demonstrate sustainability of SSEP in specific scenarios. Governmental policies are needed to support small-scale ethanol production.